2018
DOI: 10.1371/journal.pone.0192668
|View full text |Cite
|
Sign up to set email alerts
|

Imidacloprid soil movement under micro-sprinkler irrigation and soil-drench applications to control Asian citrus psyllid (ACP) and citrus leafminer (CLM)

Abstract: Imidacloprid (IM) is used to control the Asian Citrus Psyllid (ACP) and citrus leafminer (CLM), which are related to the spread of huanglongbing (HLB or citrus greening) and citrus canker diseases, respectively. In Florida citrus, imidacloprid is mainly soil-drenched around the trees for proper root uptake and translocation into plant canopy to impact ACP and CLM. The objective of this study was to determine the effect of imidacloprid rate, and irrigate amount on concentration of imidacloprid in the soil follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
6
1
1
Order By: Relevance
“…Another study found a mean lethal concentration of 0.0001 g L −1 for thiamethoxam applied in a liquid diet for insects in the laboratory [26]. Although the LC 50 found by these authors is lower than that in the present study, the application via drench can be affected by other factors, such as heavy rainfall and irrigation systems that can cause soil leaching [43].…”
Section: Discussioncontrasting
confidence: 71%
“…Another study found a mean lethal concentration of 0.0001 g L −1 for thiamethoxam applied in a liquid diet for insects in the laboratory [26]. Although the LC 50 found by these authors is lower than that in the present study, the application via drench can be affected by other factors, such as heavy rainfall and irrigation systems that can cause soil leaching [43].…”
Section: Discussioncontrasting
confidence: 71%
“…Plenty of studies focused on evaluation of control efficacy of many single insecticides via different application methods against ACP have been documented. 19,27,29,30,[53][54][55][56][57][58][59][60][61][62] For example, a single foliar spray of chlorpyrifos, fenpropathrin and oxamyl before spring growth significantly reduced ACP adults at an average of 10-to 15-fold over 5-6 months compared to untreated trees. 61 Pan et al 57 reported that foliar sprays of tolfenpyrad at 50 mg/kg and bifenthrin at 22.5 mg/kg provided excellent control efficacies of 95.3 to 99.8% and 91.3 to 99.1% against ACP within 14 DAT, respectively, which were both greater than those of tolfenpyrad at 50 mg/kg (79.02 to 91.36%) and bifenthrin at 30 mg/kg (82.86 to 91.65%) within 15 DAT, in this study (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…At present, neonicotinoids are widely used to sustainably manage ACP because of their key trait of long retention circulating within the vascular system of a citrus tree, 29,30,56,58,59 whose residues can move into new flushes fed preferentially by ACP. Fletcher et al 58 found that significant reductions of ACP population were observed about 2 weeks after imidacloprid soil-drench applications at 550 g/L, and under continued control for 4 to 8 weeks. Cheng et al 35 reported that a thiamethoxam soil-drench application at 100 mg/mL effectively controlled ACP up to 30 DAT, but only for 7 DAT using a dinotefuran foliar spray at 150 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has advantages of decreasing the restriction of horizontal root growth and short irrigation duration [12,13]. For this reason, microsprinkler irrigation has achieved good results with total growth amount and yield in winter wheat, summer corn, lawn, seedlings, and other crops [12,[14][15][16]. However, the shape, area, and uniformity of soil wetting in the microsprinkler irrigation area are affected by wind speed.…”
Section: Introductionmentioning
confidence: 99%